Potencialidades e dificuldades no uso dos tablets como ferramenta didática: o estado da arte das pesquisas - Oliveira, Rosa Aluotto de (2014)
Technology has invaded our lives in an intense and ubiquitous way. Mobile devices - smartphones and tablets - are reaching the classrooms, either in an informal way, brought by the students, or in an institutional way, supported by school principals. However, the fact is that although experts assert that mobile devices have a meaningful powerful tools to transform learning, parents and teachers are not fully convinced of it. Thus, when it comes to integrate new technologies in the teaching process, there seems to be a huge barrier to be overcome. In the belief that there is a lack of research in this area, we have decided to do a bibliographical work in order to verify the position in which they stand and reflect on some questions present in these papers. After the research of this kind of state of the art, we highlight, at the end, what the main observations and conclusions are, and also the possible research gaps as suggestions for future papers. Aiming at bringing further discussions, we have selected 39 papers among national and international articles, dissertations and theses to carry out the analysis, indicating towards the end the main questions which were raised. From this analysis we conclude that the researches on the use of tablet in the classroom have not made much progress yet and we have few concrete results, mainly regarding the improvement of students´ academic performance. If the tablet will be a tool to help change education, it is still a question to be answered; what we can infer is that this tool has the capability to support collaborative work, learning in and outside classroom and to increase student´s autonomy in the search of information and knowledge construction